Identification of lactic acid bacteria from chili bo, a Malaysian food ingredient - Leisner, Jørgen J.; Pot, Bruno; Christensen, Henrik; Rusul, Gulam (American Society for Microbiology, 1999)
Ninety-two strains of lactic acid bacteria (LAB) were isolated from a Malaysian food ingredient, chili bo, stored for up to 25 days at 28°C with no benzoic acid (product A) or with 7,000 mg of benzoic acid kg-1 (product B). The strains were divided into eight groups by traditional phenotypic tests. A total of 43 strains were selected for comparison of their sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) whole-cell protein patterns with a SDS-PAGE database of LAB. Isolates from product A were identified as Lactobacillus plantarum, Lactobacillus fermentum, Lactobacillus farciminis, Pediococcus acidilactici, Enterococcus faecalis, and Weissella confusa. Five strains belonging to clusters which could not be allocated to existing species by SDS-PAGE were further identified by 16S rRNA sequence comparison. One strain was distantly related to the Lactobacillus casei/Pediococcus group. Two strains were related to Weissella at the genus or species level. Two other strains did not belong to any previously described 16S rRNA group of LAB and occupied an intermediate position between the L. casei/Pediococcus group and the Weissella group and species of Carnobacterium. The latter two strains belong to the cluster of LAB that predominated in product B. The incidence of new species and sub-species of LAB in chili bo indicate the high probability of isolation of new LAB from certain Southeast Asian foods. None of the isolates exhibited bacteriocin activity against L. plantarum ATCC 14917 and LMG 17682.